The Civilizational Rift and the Idea of the Turkish Model: A Case Study (2002-2014) - Fatima Sajjad; Umbreen Javaid (Journal of Political Studies, 2016)
The idea of the Turkish model and the idea of clash of civilizations appeared in the International Relations academic discourse around the same time. Initially during the post- cold war days and later during the post 9/11 years the two ideas prevailed side by side. At a time when the global war on terror was seen as an evidence of an inevitable clash between Islam and the West, the idea of the Turkish model showed the possibility of reconciliation between the two. The current study examines the case of the idea of the Turkish model through the theoretical lens provided by the clash of civilizations narrative. It undertakes a cross sectional, comparative discourse analysis of the idea of the Turkish model as constructed by academics from the West, the Muslim world and Turkey. The analysis finds that contrary to the clash of civilizations narrative, the academic discourse from the West, the Muslim world and Turkey tends to present similar ideas on and around the Turkish model through various phases of the extended AKP rule in Turkey. It is compatibility rather than a clash of ideas which emerges as a dominant trend in the academic discourse across civilizations.